A selecting of a suitable CHARTIS EUROPE S.A. product by using multi criteria decision making - Jirousková, Nikola; Šindelářová, Irena; Kořenář, Václav, 1944-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2012)
This thesis addresses the question of whether it is good to insure as a young man who pays very small amount or interest to the insurance when a person goes into retirement and when the injury heals worse and longer. The target of this thesis is to determine which insurance product from CHARTIS EUROPE S.A. is advantageous for young and for old person. I solve this issue in the practical part of this thesis by using multi-criteria decision making.
Vedoucí práce: Irena Šindelářová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: matematické metody v ekonomii [obor bakal. práce]; bakalářské práce; bachelor's theses